The Relationship Between Menarche Age and Body Mass Index on Dysmenorrhea Pain in Young Women - Wahyuni, Annanda yuvita fitri; Fayakun Nu Rohmah (Universitas 'Aisyiyah Yogyakarta, 2023)
Dysmenorrhea can limit the social interaction and learning activities of adolescent girls, causing excessive discomfort and anxiety. The incidence of dysmenorrhea in adolescent girls is 54.89% in Indonesia. Body mass index and age of menarche are one of the risk factors for primary dysmenorrhea. The study aimed to determine whether there is a relationship between Menarche Age and Body Mass Index in Primary Dysmenorrhoea Pain. Research methods with quantitative methods. This study used an analytical survey method with a cross-sectional approach. The sampling technique used with the total sampling technique amounted to 80 adolescent female students who had menstruated. The data collection method in this study used a standard NRS pain scale questionnaire and Microtoise to determine BMI. Data analysis using Spearman rank statistical tests. The results of the study obtained were the majority of normal menarche aged 12-14 years, as many as 44 female students (55.0%), the majority of normal BMI 18.5-25 as many as 35 female students (43.8%) and the majority experienced moderate pain as many as 35 female students (46.2%) statistical test results were obtained namely 0.636 and significance 0.024. Based on this value, it can be concluded that there is no relationship between the age of menarche and dysmenorrhea pain and there is a relationship between body mass index and dysmenorrhea pain. It is recommended that students be motivated to reduce dysmenorrhea by sleeping regularly and routinely exercising 1 to 2 times a week.